2019
DOI: 10.1186/s12885-019-5621-5
|View full text |Cite
|
Sign up to set email alerts
|

Body weight loss after surgery affects the continuity of adjuvant chemotherapy for pancreatic cancer

Abstract: Background Postoperative chemotherapy is beneficial for many pancreatic cancer patients. However, some patients require dose reduction or the discontinuation of adjuvant chemotherapy because of adverse treatment-related effects. In this study, we aimed to evaluate two main outcomes. First, we evaluated the clinicopathological factors affecting patient disease-free survival (DFS) and overall survival (OS) following upfront surgery. Second, we evaluated the factors that influence the continuity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 25 publications
1
11
2
Order By: Relevance
“… 13 Hence, both preoperative and postoperative muscle mass should be considered when evaluating long‐term survival especially in GC patients undergoing gastrectomy. Indeed, few studies demonstrated that marked postoperative weight loss is a risk factor for poor prognosis in gastrointestinal and pancreatic cancers, 14 , 15 , 16 and excessive skeletal muscle loss after surgery is also a prognostic factor, 17 suggesting that surgery‐induced sarcopenia and postoperative muscle loss may be more harmful than preoperative sarcopenia in GC patients who undergo gastrectomy.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Hence, both preoperative and postoperative muscle mass should be considered when evaluating long‐term survival especially in GC patients undergoing gastrectomy. Indeed, few studies demonstrated that marked postoperative weight loss is a risk factor for poor prognosis in gastrointestinal and pancreatic cancers, 14 , 15 , 16 and excessive skeletal muscle loss after surgery is also a prognostic factor, 17 suggesting that surgery‐induced sarcopenia and postoperative muscle loss may be more harmful than preoperative sarcopenia in GC patients who undergo gastrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In fact, malnutrition is common among cancer patients, with an incidence rate ranging from 21% to 75%, as determined using different screening or assessment tools. [12][13][14] Malnutrition has a strong adverse impact on the tolerance of chemotherapy, 15 QOL, 16 complications, 17 and survival. 12 Thus, an early diagnosis and nutrition intervention are key components of strategies to improve the QOL and outcomes of patients, with interventions specifically targeting the reversible elements during the development of malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…A merit would be preserving the relative dose intensity of adjuvant chemotherapy by maintaining nutrition and immune function by preserving bowel function. Some studies have reported that nutritional status, represented by serum albumin levels, and body weight and lean body mass is considered to affect adherence of patients with PC to postoperative chemotherapy and the reduced relative dose intensity of adjuvant chemotherapy has a negative impact on postoperative survival [19] , [20] , [21] , [22] . Meanwhile, as a demerit, such conservative procedure always carries the risk of incomplete resection.…”
Section: Discussionmentioning
confidence: 99%